Implications and Presupositions in Michelle Obama's Speech: A Pragmatics Study - Dezsa Fauzah Maharanti Suryana; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study purposes to describe and observe the types of implicatures found in speech of Michelle Obama within the Democratic National Convention in 2020. Based on analytical methods and procedures the data, this study uses a qualitative method and descriptive approach, since the production of described data is in the form of written or spoken words by using the transcription. The data in this study are implicature utterances of Michelle Obama in 2020 aired in national media. The main theory of this research is Yule (2006) regarding to implicature categories and presupposition. The data were collected using the manual method of listening and note taking. This method is realized by using basic techniques and advanced techniques. The basic technique used is tapping technique as the video may be replayed several times. While the advanced technique used is the free-involvement listening technique, recording technique and note-taking technique. Based on the results of the analysis found 4 types of implicatures used in speech, yet the whole data analyzed shows only two categorizes; generalized and particularized conversational implicature. Based on the data analysis, there are 78% data show the generalized conversational implicature, while the rest 22% leads to particularized conversational implicature. It can be inferred that Michelle Obama speech in Democratic National Convention in 2020 applied generalized conversational implicature.